A set theory based fuzzy fs/QCA: a new tool for sensory analysis of foods - JK Pallavi (CyTA - Journal of Food)
A study was conducted to identify the closest possible contributors to human behavior during sensory evaluation of fortified yogurt. Following a numbers-only method, sensory scores (1–9) were assigned to four Attributes – Color, Taste, Texture and Flavor by the panel members. For the first time, set theory was used to identify a subset of the Attributes that are primarily responsible for the sensory acceptability of yogurt. fs/QCA (fuzzy set Qualitative Comparative Analysis) is an open software developed by Ragin and Davey that uses all data points singly and in combination to identify influence on Outcome. The technique gave a solution that the combination of Taste, Flavor and Texture had approximately 90% consistency with the consumer choice. Further, a parsimonious solution identified Taste as the most important contributor to sensory acceptance of yogurt. Such results would be helpful in guiding cost-effective formulation and production of foods.